Menanamkan Spiritualitas Kepemimpinan Kristiani melalui Pembelajaran Pendidikan Agama Kristen - Syukurman Zebua; Steven Tong Siburian; Denny Zakhirsyah; Stevan Andi Pinoa; Aloycius Reinhard Rende (STTI Harvest Semarang, 2025)
This study aims to examine the role of Christian Religious Education (CRE) as a strategic medium in instilling the spirituality of Christian leadership in a holistic manner. Christian leadership is understood not merely as an authoritative position, but as a calling to serve, rooted in a relationship with God and modeled on Jesus Christ as the Good Shepherd. In the educational context, particularly in CRE, the urgency of instilling leadership spirituality arises as a response to the modern tendency to focus on cognitive aspects while neglecting affective and spiritual dimensions. This research employs a literature analysis method with a thematic approach through data reduction, categorization, comparative analysis, and conceptual synthesis from theological, pedagogical, and interdisciplinary sources. The findings indicate that CRE plays an essential role in cultivating humility, integrity, exemplary conduct, courage to serve, and self-sacrifice as the primary indicators of Christian leadership spirituality. Participatory, reflective, and contextual learning strategies such as project-based learning and service learning can strengthen the internalization of Gospel values into leadership practices. CRE not only contributes to the formation of personal faith but also has a transformative impact on the church, society, and nation by nurturing leaders with Christ-like character. Thus, this study affirms that CRE serves as a vital foundation for the development of holistic, relevant, and transformative Christian leadership in the contemporary era. AbstrakPenelitian ini bertujuan menelaah peran Pendidikan Agama Kristen (PAK) sebagai media strategis dalam menanamkan spiritualitas kepemimpinan Kristiani secara holistik. Kepemimpinan Kristiani dipahami bukan sekadar posisi otoritatif, melainkan panggilan pelayanan yang berakar pada relasi dengan Allah dan keteladanan Yesus Kristus sebagai Gembala Agung. Dalam konteks pendidikan, khususnya PAK, urgensi penanaman spiritualitas kepemimpinan muncul sebagai respons terhadap kecenderungan pendidikan modern yang berfokus pada aspek kognitif, sementara aspek afektif dan spiritual terabaikan. Metode penelitian yang digunakan adalah analisis literatur dengan pendekatan tematik melalui reduksi data, kategorisasi, analisis komparatif, dan sintesis konseptual dari berbagai sumber teologis, pedagogis, dan interdisipliner. Hasil penelitian menunjukkan bahwa PAK memiliki peranan penting dalam membentuk kerendahan hati, integritas, keteladanan, keberanian melayani, dan pengorbanan diri sebagai indikator utama spiritualitas kepemimpinan Kristiani. Strategi pembelajaran partisipatif, reflektif, dan kontekstual, seperti project-based learning dan service learning dapat memperkuat internalisasi nilai Injil ke dalam praksis kepemimpinan. PAK tidak hanya berkontribusi pada pembentukan iman personal, tetapi juga berdampak transformatif bagi gereja, masyarakat, dan bangsa melalui lahirnya pemimpin-pemimpin yang berkarakter Kristus. Dengan demikian, penelitian ini menegaskan bahwa PAK merupakan fondasi penting bagi pengembangan kepemimpinan Kristiani yang holistik, relevan, dan transformatif di era kontemporer.